Causal variant loci and protein-coding genes for soybean bacterial pustule resistance in the flowering stage - Fonseca,Pollyanna Capobiango da (2022)
Abstract Bacterial pustule is an important soybean disease caused by Xanthomonas citri pv. glycines, but information about genetic resistance to this pathogen is scarce. This study aimed to investigate soybean genetic resistance to bacterial pustule in the flowering stage through association analysis, characterization of candidate SNP markers, and identification of protein-coding genes potentially regulating defense processes. Therefore, 109 soybean cultivars genotyped with a 6k Illumina platform were assessed for disease severity. A genome-wide analysis revealed a total of 13 SNPs significantly associated. Through protein annotation, we identified three markers located inside the coding regions of uncharacterized protein LOC100779077, histone-lysine N-methyltransferase SUVR4, and ABC-transporter B family member-9. Nucleotide polymorphism on the first two of these markers produces a non-synonymous polymorphism with polarity shift from hydrophobic to polar amino acid. It is convenient to prioritize these three candidate markers for validation procedures with the purpose of using them in marker-assisted soybean breeding programs.